2007
DOI: 10.1007/s10290-007-0099-7
|View full text |Cite
|
Sign up to set email alerts
|

Location: A Neglected Determinant of Firm Growth

Abstract: Agglomeration, knowledge resources, firm growth,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(57 citation statements)
references
References 29 publications
2
51
1
1
Order By: Relevance
“…Research which expands beyond the industry has focused largely on HGF activity in one country (see Bornhäll et al 2015;Siepel et al 2015;Bos and Stam 2014;Garcia and Puente 2012;Hölzl 2011;Falkenhall and Junkka 2009;Moreno and Casillas 2007;Littunen and Tohmo 2003), one region (Desai and Motoyama 2015;Mason and Brown 2010) or one or a few sectors (Siepel et al 2015;Coad and Rao 2008;Littunen and Tohmo 2003). Some comparative empirical research has shown that region-specific characteristics, like industrial diversity, agglomeration economies and employment (Bogas and Barbosa 2013;Audretsch and Dohse 2007), play an important role in explaining the variance in HGF activity across regions. This indicates that variation at the regional or supraregional levels of analysis is an important question.…”
Section: Theoretical Foundationmentioning
confidence: 97%
“…Research which expands beyond the industry has focused largely on HGF activity in one country (see Bornhäll et al 2015;Siepel et al 2015;Bos and Stam 2014;Garcia and Puente 2012;Hölzl 2011;Falkenhall and Junkka 2009;Moreno and Casillas 2007;Littunen and Tohmo 2003), one region (Desai and Motoyama 2015;Mason and Brown 2010) or one or a few sectors (Siepel et al 2015;Coad and Rao 2008;Littunen and Tohmo 2003). Some comparative empirical research has shown that region-specific characteristics, like industrial diversity, agglomeration economies and employment (Bogas and Barbosa 2013;Audretsch and Dohse 2007), play an important role in explaining the variance in HGF activity across regions. This indicates that variation at the regional or supraregional levels of analysis is an important question.…”
Section: Theoretical Foundationmentioning
confidence: 97%
“…Conversely, depressed rates of local employment and income are likely to reduce the performance of firms, as well as reducing alternative employment opportunities (Gimeno et al 1997;Fotopoulos and Louri 2000;Audretsch and Dohse 2007). Thus, local economic conditions influence both the performance of enterprises and the threshold of performance through the outside options available (Figure 2).…”
Section: Silva and Mccomb 2012)mentioning
confidence: 99%
“…Furthermore, little is known about the impact of location on the growth of firms (Acs and Armington 2004;Audretsch and Dohse 2007;St-Jean et al 2008; Barbosa and Eiriz 2011;Bogas and Barbosa 2013). There are some studies that analyse the location of HGFs at regional level or in urban areas (Acs and Mueller 2008) although there is still not enough evidence about the influence of spatial agglomeration areas on the location of HGFs.…”
Section: Introductionmentioning
confidence: 98%
“…A review of the literature on HGFs Location as a factor in the development of high-growth firms Location is considered an influential factor in the development of HGFs as this process can depend on the characteristics of the geographical environment (Acs and Armington 2004;Hoogstra and van Dijk 2004;Audretsch and Dohse 2007;St-Jean et al 2008;Barbosa and Eiriz 2011;Bogas and Barbosa 2013).…”
Section: Introductionmentioning
confidence: 99%